2015
DOI: 10.1515/cclm-2015-0668
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-zymography: a still worthwhile method for gelatinases analysis in biological samples

Abstract: Matrix metallo-proteinases (MMPs) are a family of zinc-dependent endopeptidases, capable of degrading all the molecular components of extracellular matrix. A class of MMPs is gelatinases which includes gelatinase A or MMP-2 (72 kDa) and gelatinase B or MMP-9 (92 kDa), which have been shown to play critical roles in pathophysiology of many human disease and, in particular, cancer progression. For these reasons they obtained a great interest as potential non-invasive biomarker in providing useful clinical inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 37 publications
0
25
1
Order By: Relevance
“…Our study confirms that miR-194 inhibited epithelial marker E-cadherin and increased mesenchymal markers vimentin and MMP-2. Moreover, zymography assay was performed in our study, which allows one to measure the relative amounts of active and inactive enzymes,33 and results showed that miR-194 significantly increased the gelatin-degrading activity of MMP-2. These data suggest that miR-194 is an EMT promoter in CRC cells.…”
Section: Discussionmentioning
confidence: 95%
“…Our study confirms that miR-194 inhibited epithelial marker E-cadherin and increased mesenchymal markers vimentin and MMP-2. Moreover, zymography assay was performed in our study, which allows one to measure the relative amounts of active and inactive enzymes,33 and results showed that miR-194 significantly increased the gelatin-degrading activity of MMP-2. These data suggest that miR-194 is an EMT promoter in CRC cells.…”
Section: Discussionmentioning
confidence: 95%
“…MMPs have overlapping substrate specificities. Even so, they are divided into five groups according to their preferential degradation of different matrix substrates: matrilysin (MMP7 and MMP26), collagenases (MMP1, MMP8, MMP13, MMP18), gelatinases (MMP2 and MMP9), stromelysin (MMP3, MMP10, MMP11), and membrane MMPs (MT‐MMPs, MMP14, MMP15, MMP16, MMP17, MMP23A, MMP23B, MMP24, MMP25) . These proteases not only target ECM proteins but they are also involved in the regulation of inflammatory signaling pathways .…”
Section: Comparative Analysis Of Proteases Distribution Among Distincmentioning
confidence: 99%
“…Gelatinolytic activity was performed as previously described [ 16 ]. Briefly, total protein (25 µg) of each sample was mixed with sample buffer (10 mM Tris–HCl pH 6.8, 12.5 % SDS, 5 % sucrose, 0.1 % bromophenol blue) and applied directly without prior heating or reduction to 7.5 % (w/v) acrylamide gels containing 0.3 % (w/v) of gelatin.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the character of proteolytic bands was analyzed by incubating the identical zymograms in 0.1 mg/ml of PMSF, a serine protease inhibitor; or 2 mM Pefabloc, an irreversible serine protease inhibitor. Following zymography, the degree of gelatin digestion was quantified as previously described [ 16 ]. Briefly, we used an image analysis software (ImageQuant TL, Amersham Bioscience, Chicago, IL, USA) according to the manufacturer’s specifications.…”
Section: Methodsmentioning
confidence: 99%